Effect of Moina sp. Enrichment with Fishmeal on the Growth of Nile Tilapia (Oreochromis niloticus) Juveniles - Said Ali Akbar; Abdillah Del Mayda; Nanda Muhammad Razi (JURNAL AKUAKULTURA, 2026)
This study evaluated the effectiveness of enriching Moina sp. with fishmeal as a natural feed to enhance the growth performance of Nile tilapia (Oreochromis niloticus) juvenile. A completely randomized design was applied with five treatments and four replicates, consisting of unenriched Moina sp., and enrichment levels of 6 g/L, 8 g/L, 10 g/L and 12 g/L fishmeal. Observed parameters included absolute length growth, absolute weight gain, specific growth rate (SGR) and survival rate. The results indicated that the treatments produced different growth responses, with the 8 g/L enrichment yielding the highest performance, producing an absolute length of 1.37 ± 0.457 cm, absolute weight of 1.32 ± 0.155 g and SGR of 4.93 ± 0.219 % per day. ANOVA demonstrated significant effects on absolute length, absolute weight and SGR (p < 0.05), while survival rate, ranging from 90.00–97.50 %, showed no significant differences among treatments (p > 0.05). Water quality parameters remained within suitable ranges throughout the culture period. Overall, enrichment of Moina sp. with fishmeal at 8–10 g/L exhibits strong potential as a strategy to improve the nutritional value of natural feed. This approach also aligns with sustainable aquatic resource management within the framework of SDGs 14.